Green Deen : What Islam Teaches about Protecting the Planet. - Abdul-Matin, Ibrahim; Ellison, Keith (San Francisco : Berrett-Koehler Publishers, 2010)
"The Earth is a mosque"Muslims are compelled by their religion to praise the Creator and to care for their community. But what is not widely known is that there are deep and long-standing connections between Islamic teachings and environmentalism. In this groundbreaking book, Ibrahim Abdul-Matin draws on research, scripture, and interviews with Muslim Americans to trace Islam's preoccupation with humankind's collective role as stewards of the Earth. Abdul-Matin points out that the Prophet Muhammad declared that "the Earth is a mosque."Deen means "path" or "way" in Arabic. Abdul-Matin offers do.
Contents; Foreword; Preface: This Deen Called Islam; Introduction: The Earth Is a Mosque; Part I: Waste; Part Ii: Watts; Part Iii: Water; Part Iv: Food; Conclusion: Following the Call; Notes; Glossary of Islamic Terms; Resources; Acknowledgments; Index; About the Author.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 650
Keywords: Environmental protection -- Religious aspects -- Islam; Nature -- Religious aspects -- Islam; Sustainable living; Religion; Environmental protection; Islam; Nature; Religious aspects; Religion; Environmental protection -- Religious aspects -- Islam; Nature conservation -- Religious aspects -- Islam; Environmentalism -- Religious aspects -- Islam; Sustainable living; RELIGION -- Islam -- General; NATURE -- Ecology; Environmental protection -- Religious aspects -- Islam; Nature -- Religious aspects -- Islam; Religion; Sustainable living; Electronic books